2014
DOI: 10.6090/jarq.48.87
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies on Intestinal Protozoa in Pigs in Saitama, Japan

Abstract: studies on the induction of diarrhea by protozoa 13,26 . In this study, we investigated swine parasitism by Cryptosporidium, Giardia, Balantidium, and coccidium by calculating the number of oocysts and cysts per gram of stools in 334 pigs and analyzing the relationships between the detection rate and age group. The stool condition score was also analyzed to investigate the relationship between infection and diarrhea. Using the results of this, the first systematically classified study of swine protozoan infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…B. coli is distributed worldwide, and its main host is pigs [ 7 ]. Previous studies have reported the prevalence of B. coli in domestic pigs in different countries including 46.4% and 84.1% in Japan (155/334 and 212/252, respectively), 93.0% in India (93/100), 16.8% in China (94/560), 40.0% in Bangladesh (44/110), 1.6%, in Turkey (4/238), 51.5% in Nigeria (207/402), 64.1% in Kenya (196/306), 0.7% in Germany (2/287), 61.6% in Italy (149/242), and 60.9% in Brazil (236/387) [ 8 , 21 , 22 , 23 , 24 , 25 ]. The prevalence in domestic pigs is highly variable, ranging from 0.7% to 93.0%, and might be affected by the breeding system, hygiene conditions, season, diagnostic method, and climate.…”
Section: Discussionmentioning
confidence: 99%
“…B. coli is distributed worldwide, and its main host is pigs [ 7 ]. Previous studies have reported the prevalence of B. coli in domestic pigs in different countries including 46.4% and 84.1% in Japan (155/334 and 212/252, respectively), 93.0% in India (93/100), 16.8% in China (94/560), 40.0% in Bangladesh (44/110), 1.6%, in Turkey (4/238), 51.5% in Nigeria (207/402), 64.1% in Kenya (196/306), 0.7% in Germany (2/287), 61.6% in Italy (149/242), and 60.9% in Brazil (236/387) [ 8 , 21 , 22 , 23 , 24 , 25 ]. The prevalence in domestic pigs is highly variable, ranging from 0.7% to 93.0%, and might be affected by the breeding system, hygiene conditions, season, diagnostic method, and climate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the close association between pigs and humans enables cross-infection with a range of zoonotic parasites like Tae nia solium, Trichinella spiralis and Toxoplasma gondii, all of which contribute deleteriously to human health. Pigs are infected with wide range of gastrointestinal (GI) parasites with reports from all corners of the world (Permin et al, 1999;Tamboura et al2006;Lai et al, 2011;Navarro-Gonzalez et al, 2013;Yui et al, 2014;Alynne et al, 2015;Junhui et al, 2015;Kabululu et al, 2015;) including India (Laha et al, 2014;Dadas et al, 2016;Joute et al, 2016;Krishna Murthy et al, 2016;Singh et al, 2017;Patra et al, 2019). Age, sex of animal, management practices and geographical location are the major risk factors associated with GI parasites in pigs (Permin et al, 1999;Geresu et al, 2015;Roesel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“… Yui et al . 2014 [ 183 ] 1– <2 mo 29 Weaned 8 (27.6) 2–6 mo 190 finished 62 (32.6) Sows, Sow candidates 76 2 (2.6) <1 mo 55 Pre-weaned 15 (27.3) 2 C. suis ; C. scrofarum Totally; out of 344 examined pigs, 112 were infected (32.6%). Yui et al .…”
Section: Reported Animal Cases Of Cryptosporidiosis Species Diversitmentioning
confidence: 99%